Menakar Efektivitas Bantuan Sosial Terhadap Pemenuhan Kebutuhan Masyarakat Terdampak COVID-19 di Kota Malang - Yanuarita, Heylen Amildha; Djoko susanto, Djoko (JISIP: Jurnal Ilmu Sosial dan Pendidikan, 2021)
The Social Assistance Program is assistance originating from the Ministry of Social Affairs of the Republic of Indonesia which is then provided to the community based on Integrated Social Welfare Data (DTKS). The purpose of this research is to find out how effective the implementation of the Social Assistance program is in meeting the needs of people affected by COVID-19 in Malang City. Factors that hinder the implementation of social assistance programs. The theory used in this research is the theory of program effectiveness by Budiani using 4 indicators (Program Objectives, Program Socialization, Target Accuracy, Program Monitoring). This problem was answered by the researcher using a qualitative method with a descriptive approach. This study used data collection techniques in the form of observation, documentation and then analyzes according to the problem to be investigated by the researcher. The results of this study indicated that the effectiveness of social assistance against COVID 19 in Malang City is seen from 4 indicators (Program Objectives, Program Socialization, Target Accuracy, Program Monitoring) which are not yet effective. The inhibiting factor in this study was the validation and the program that was issued suddenly.